The Effectiveness of Rehabilitation Programs of Learning Disabilities on Children with Attention Deficit Hyperactivity Disorder - Mohamed Ali Saad Baraka; Eman Roshdy El-Safy Dalia; Sherif Kamel Bahaa El-Dine; Maha Mahmoud Rabie (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Objective: The aim of this work is to evaluate the role of rehabilitation programs of learning disabilities on children with attention deficit hyperactivity disorder (ADHD) children, and compare the effect of pharmacological treatment, rehabilitation program of learning disabilities, and both together on children with attention deficit hyperactivity disorder (ADHD) children.  Design: A prospective study.  Setting: Zagazig University Hospitals.  Patients and methods: This study was conducted on a sample of 30 ADHD children between the ages of 6.5 to 8.5 years, attending the Units of Phoniatrics in Ain Shams University Hospital and Zagazig University Hospital. These children demonstrated skills below the performance range expected for their age on pretest measures and school assessments.  Results: After testing the control groups with age ranged (5.5-8.5y) (mean =7) with dividing them in to 3 equal groups in age , and recording their testing as normal, the ADHD children tested per/ post study. The 1st group exposed for pharmacological treatment; their pretest was low in comparison for same age groups. There were increased result of posttest by about 10-30% (mean=20) in their tests in group 2 children remediated by rehabilitation program and pretests were done and were low for normal control group in same age. The posttests were elevated by about 20-30% (mean=25%) In group 3 children remediated by rehabilitation program and pretests were done and were low for normal control group in same age. The posttests were elevated by about 30-40% (mean=30%) After comparing the results of 3 groups; there were no significant deference in pretests result. There was high significant difference in posttests result except in Stanford Binnet Intelligence Scale "4th Arabic version". There were no significant deference between male and female children.  Conclusion: ADHD affects learning globally and compromises all cognitive functions, rather than just one or two. There were good the role of rehabilitation programs of learning disabilities on children with attention defi cit hyperactivity disorder (ADHD) children, and by adding pharmacological treatment the better results were produced.